ISTIFĀDAH AL-TA'LĪM AL-ILIKTRŪNĪ FĪ TA'LĪM AL LUGAH AL-'ARABIYAH LI GAIR AN-NĀṬIQĪNA BIHĀ - rahmaniah rahmaniah (UIN ANTASARI, 2020)
This study aims to explain how the use of E-Learning in learning Arabic and explain how the learning outcomes of class VIII students in learning Arabic using E-Learning and to explain what are the advantages and disadvantages of E-Learning in learning Arabic for class VIII students at MTsN 3 Banjarmasin. This research is a type of qualitative descriptive research, with the data collection process using the methods of observation, interviews and documentation. This study interviewed one Arabic teacher and 32 students in class VIII MTsN 3 Banjarmasin. Based on the results of the study that the use of e-learning in learning Arabic is very beneficial for teachers and students and is also very helpful in learning. Students become more active and independent in learning using e-learning. And the learning outcomes of class VIII students in learning Arabic using E-Learning are varied, some get above average scores and some below average. And the advantage of e-learning is that you can easily find out and view information related to learning Arabic. E-learning is also without being limited by distance, place and time. Students also become more active in participating in learning. Meanwhile, the lack of e-learning is that not all internet networks are smooth, so when opening or using it, problems can occur, namely errors can occur. And there is less interaction between teachers and students because they cannot meet face to face.